Global longitudinal strain as an Indicator of cardiac Iron overload in thalassemia patients - Firoozeh Abtahi; Alireza Abdi; Saideh Jamshidi; Mehran Karimi; Mohammad Ali Babaei-Beigi; Armin Attar (Cardiovascular Ultrasound, 2019)
Abstract Background and objective Cardiac involvement due to iron overload is the most common cause of morbidity and mortality in patients with thalassemia, and many patients remain asymptomatic until the late stages. Therefore, early detection of heart problems in such patients at subclinical stages can improve the prognosis of these patients. We investigated the role of speckled tracking (SI) and tissue Doppler echocardiography (TDI) in early detection of iron overload in these patients. Methods 52 thalassemic patients who were receiving regular blood transfusion with normal global LV function were examined by two- and three-dimensional echocardiography. Cardiac MRI was done and T2* images were considered as the non-invasive gold standard for evaluating cardiac iron deposition. Serum ferritin level was assessed and the relationships between serum ferritin levels and echo finding with cardiac MRI T2 * was investigated. Results No significant relationship was seen between serum ferritin levels and cardiac MRI T2 *. Among the echocardiographic findings, septal systolic myocardial velocity (P = 0.002 and r = 0.43) and global strain (GLS) (P = 0.000 and r = 0.60) were significantly associated with T2 *. A GLS < 19.5 could predict a T2 * level below 20 by 82.14% sensitivity and 86.36% specificity (area under the curve = 0.87; p < 0.0001). Conclusion While serum ferritin level and ejection fraction are not useful candidates, GLS may be used as a valuable marker to screen thalassemia patients for myocardial iron deposition, using a cut off value below − 19.5. This approach may facilitate the cardiac follow up, reduce the costs, and contribute to preventing deterioration of cardiac function in countries with limited availability of cardiac MRI.